Intrinsic self-healing polymers with a high E-modulus based on dynamic reversible urea bonds - Zechel, Stefan; Geitner, Robert; Abend, Marcus; Siegmann, Michael; Enke, Marcel; Kuhl, Natascha; Klein, Moritz; Vitz, Jürgen; Gräfe, Stefanie; Dietzek, Benjamin; Schmitt, Michael; Popp, Jürgen; et al. (NPG Asia materials, 2017)
The straightforward synthesis of a urea polymer network is presented. Commercially available monomers are polymerized using light-induced polymerization, resulting in networks crosslinked by hindered urea molecules. These moieties are reversible and, thus, can be converted into the starting compounds (that is, isocyanate and amine) by a simple thermal treatment. This process is monitored using differential scanning calorimetry as well as Raman and infrared spectroscopy. Furthermore, the self-healing ability of these polymer networks is investigated using scratch-healing tests as well as bulk-healing investigations using tensile testing. The resultant materials have a high E -modulus, are able to heal scratches at temperatures above 70 °C multiple times and their mechanical properties can be partially regenerated. The underlying healing mechanism is based on the reversible opening of the urea bonds and exchange reactions between two functional groups, which were confirmed from a spectroscopic analysis. In summary, these new materials are a new type of intrinsically healable polymers and provide a first step toward hard and healable polymers. Self-healing polymers: Learning the hard stuff One of the hardest self-healing polymers ever reported has been prepared using the reversible bonds of sterically hindered urea groups. Polymers that can re-form internal chemical links after being scratched or cracked are usually subject to design constraints that lower their mechanical strength. To overcome these constraints, Martin D. Hager and colleagues from Friedrich Schiller University Jena, Germany, created a series of poly(methacrylate) polymers bearing reversible urea units. By simply exposing the starting reagents to brief flashes of light, they prepared a cross-linked polymer featuring the urea units on the poly(methacrylate) chains resulting in mechanically tough materials. After optimizing the cross-link density, the team deliberately scratched the polymer and then heated it to begin the self-healing process. Temperatures of about 100 degree Celsius were sufficient to open urea bonds up and initiate material repair. New intrinsic self-healing polymers with outstanding mechanical performance are presented. For this purpose, sterically hindered amines were utilized to crosslink isocyanate containing poly(methacrylates) resulting in urea crosslinked networks. The reversibility of the urea bond during thermal treatment could be utilized to induce self-healing ability and could be proven using various techniques.